The Effect of Freezing Time on the Melting Time of Ice Blocks at PT Siantar Ice Factory - Calvin Klein Sitanggang; Tambos August Sianturi (Journal of Engineering Science and Technology Management (JES-TM), 2026)
The background of this study is based on the needs of the ice block industry for products with higher resistance to melting in order to maintain distribution quality and improve operational efficiency. This research aims to analyze the effect of freezing duration on the melting time of ice blocks and to determine the most optimal freezing time among 24 hours, 27 hours, and 30 hours. The research methodology employs a mixed-method approach through direct observation conducted during Field Work Practice (PKL). Quantitative data were obtained from measurements of the melting time of ice blocks produced under three different freezing durations with three repetitions, while qualitative data were collected from observations of the freezing process and the physical condition of the ice. The freezing process was carried out at a temperature range of −10°C to −15°C using a brine-based cooling system. The results indicate that freezing for 24 hours produces an average melting time of 8.5 hours, freezing for 27 hours results in an average melting time of 10.2 hours, and freezing for 30 hours results in an average melting time of 12.5 hours. These findings demonstrate that longer freezing durations lead to increased melting time of ice blocks. Freezing for 30 hours provides the longest melting time and is considered the most optimal in enhancing resistance to melting.